KAJIAN SISTEM PENGANGKUTAN SAMPAH KABUPATEN MAGETAN - Dewi Dwirianti (Purifikasi, 2005)
Magetan Municipality with the average of solid generation was 2L/person/day .The methods used in the study were interview and observation to all solid waste transport vehicles. Analysis of the technical aspect analysis included transportation time, efficiency, number of vehicles, amount of transported solid waste, existing route, alternatives for service area development and route improvement. This study showed that the waste transport efficiencies of the dump trucks and the manual trucks could be increased from the existing 1 to 2 trips/day. Additionally, the efficiency of the pick up vehicle could be increased from 1 to 3 trips/day. In the solid waste transport using Hauled Container System (HCS), the efficiency could be increased from 4 to 6 trips/day using the current off route factor, and increased to 8 trips/days with the reduction of off factor from 0,38 to 0,18.